Coronary-Cameral Fistula as a Cause of Post-Infarction Left Ventricular Aneurysm: Current State of the Problem and Diagnostic Search - Gogayeva, Olena K.; Nudchenko, Oleksandr O. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Coronary artery disease (CAD) is predominantly develops due to atherosclerotic stenosis of the arterial lumen but a special place hold coronary arteries anomalies, among which distinguish coronary artery fistulas (CAF). While 90% of CAFs are congenital, the remaining cases are acquired. Most CAFs remain asymptomatic, but in some cases, they can lead to heart failure, arrhythmias, shortness of breath, angina pectoris, or infective endocarditis. The pathogenetic mechanism of ischemia in the absence of coronary artery stenosis is the phenomenon of coronary steal. CAFs of medium and large size are typically symptomatic. Fistula connections from the distal coronary artery are more frequently aneurysmal and are associated with a high risk of thrombosis and myocardial infarction. In patients with symptoms of CAD or heart failure, closure of the CAF is recommended. Case description. A 45-year-old male patient was hospitalized at the Institute with symptoms of unstable angina and heart failure. His medical history included a Q-wave myocardial infarction two years prior. ECG revealed post-infarction cardiosclerosis of the anterior-septal-apical region of the left ventricle (LV) with septal ischemia. Echocardiography demonstrated dilatation of the heart chambers, a dyskinetic LV aneurysm, and significantly reduced contractility (LV ejection fraction: 22–24%). Color Doppler imaging identified a coronary-cameral fistula originating from the distal segment of the left anterior descending artery (LAD) and draining into the right ventricle. Coronary angiography confirmed the presence of a coronary-cameral fistula from the distal LAD. Based on the findings, on-pump surgical intervention was recommended for the patient. Conclusions 1. A coronary-cameral fistula from the LAD to the right ventricle can lead to Q-wave myocardial infarction with subsequent development of a left ventricular aneurysm. 2. A distally located CAF is associated with a progressive and symptomatic disease course. 3. Clinical manifestations of CAF include angina pectoris, shortness of breath, paroxysmal ventricular tachycardia, and heart failure. To alleviate anginal symptoms, long-acting nitrates are recommended. 4. The presence of a coronary-cameral fistula can be suspected auscultatory (systolic-diastolic murmur), detected by echocardiography with color Doppler, and confirmed angiographically.